ANALISIS WACANA KRITIS PERSPEKTIF KALIMAT DALAM TALK SHOW MATA NAJWA TENTANG UU OMNIBUS LAW CIPTA KERJA DI TRANS7 - Deri Wan Minto (STKIP Siliwangi, 2022)
The background of this research seen from the mass media, especially television, has become a necessity in addressing the perspectives that occur in society. Television can determine the ideology, interests and points of view to influence others. This study aims to describe Najwa Shihab's partisanship, social cognition, and context in the Mata Najwa event at Trans7 regarding the Omnibus Law: Job Creation in Trans7 Model Teun A. Van Dijk. This type of research is qualitative with a Critical Discourse Analysis (AWK) system approach. The data is in the form of speeches from the presenters in the Mata Najwa program with the concept of taking part in the host, whether to the